The impact of employees' work life balance reviewed from work from home during Covid-19 Pandemic / Effa Nadhirah Roslee, Izzatur Najlaa Ismail and Jennifah Nordin - Roslee, Effa Nadhirah; Ismail, Izzatur Najlaa; Nordin, Jennifah (2021)
Coronavirus widespread at end of December 2019 has forced most public and private agencies worldwide to limit face-to-face interaction by allowing the employee to work from home (WFH). The new norm required an employee's ability to balance between work-related demand and non-work-related demand or known as work-life balance (WLB). Ideally, work from home can bring positive effect on the work-life balance of the employees during covid- 19 because they can strengthen the family relationships, have their own time personal space such as to maintain body, mind, and spirit, make employees feel satisfied, increase team performance, and can increase employees work-life balance. (Bataineh, 2019, Khotimah & Yusuf, 2021). Even two-third of the Malaysian workforce supports the continuation of work from home arrangement during the post-movement control order (MCO) period (The Star, 2020). However, there was a different scenario on the work-life balance of employees in Malaysia during the covid-19 pandemic. According to the 2019 work-life index, published by tech company Kisi, Kuala Lumpur was found to have the worst work-life balance out of 40 major cities around the globe. The employees in Malaysia experience a bad work-life balance due to the new occupational setting where work from home is a challenge for them (Bernama, 2021). Those who work from home faced higher levels of stress as they need to encounter different kinds of challenges at home (New Straits Time, 2020). Thus, the purpose of this paper is to highlight the findings based on the review of the literature related to the impact of work from home on the employees' work-life balance during the Covid-19 pandemic. The findings led to suggestions on what needs to be done by the employer in facing this new work setting.